Analysis of Collaboration, Communication, Technology, Proficiency, Teamwork, Results, and Potential of Different Generations’ Joint Work - Bhatwadekar, Kalpana (Digital Repository of Theses, 2025)
The research seeks to examine how various generations cooperate, communicate, utilize technology, work as a team, and unlock their potential in a multigenerational workplace Introduction to Multigenerational Workforce: The research addresses the challenges organizations face with a multigenerational workforce, particularly with the entry of Gen Z into the job market. It aims to provide tools for aligning organizational policies and procedures in accordance with the expectations of different generations. Generational Definitions: The study focuses on three generations: Gen X (1965-1979), Gen Y (1980-1996), and Gen Z (1997-2012), each with distinct characteristics and expectations that influence their work-life. Research Objectives: The primary objective is to understand the workplace expectations of these generations concerning leadership, culture, communication, job satisfaction, and compensation benefits. Methodology: The research methodology includes a literature review, and a survey conducted at Sirmaxo Chemicals Pvt Ltd, a pharmaceutical firm with 240 employees. The survey aims to analyze generational expectations and their impact on workplace dynamics. Survey Design: A questionnaire with 17 questions is prepared to capture the generational traits and workplace expectations of employees. The survey also considers variables like work location, demography, and total work experience. Demographic Distribution: The workforce at Sirmaxo is categorized into Gen X (21%), Gen Y (73%), and Gen Z (6%), with a gender distribution of 85% males and 15% females. Workplace Expectations: The research seeks to understand how different generations perceive organizational support, leadership, value alignment, and job importance, among other factors. Impact of Work Location: The study also examines how workplace location (corporate office, manufacturing plant, or sales team at Pan India locations) influences generational expectations and satisfaction.Total experience of employees: the study reviews the influence of total work experience of the employee on the response to the survey. Preliminary Literature Review: The literature review highlights the importance of understanding multigenerational behavior at the workplace and the need for organizations to adapt to generational changes. Conclusion and Implications: The findings aim to support MSMEs in India by providing insights into creating a harmonious and productive work environment for a multigenerational workforce, ultimately aiding in talent retention and organizational growth.